2015
DOI: 10.1007/s10509-015-2429-x
|View full text |Cite
|
Sign up to set email alerts
|

Dilatonic equation of hydrostatic equilibrium and neutron star structure

Abstract: In this paper, we present a new hydrostatic equilibrium equation related to dilaton gravity. We consider a spherical symmetric metric to obtain the hydrostatic equilibrium equation of stars in 4-dimensions, and generalize TOV equation to the case of regarding a dilaton field. Then, we calculate the structure properties of neutron star using our obtained hydrostatic equilibrium equation employing the modern equations of state of neutron star matter derived from microscopic calculations. We show that the maximum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 79 publications
(67 reference statements)
1
29
0
Order By: Relevance
“…It was shown that the maximum mass of neutron star is about 1.68M ⊙ . In addition, the EoS with dilaton gravity was employed and the properties of neutron star were investigated [56]. The results showed that by increasing the effects of dilaton gravity, the maximum mass of this star decreases (M max ≤ 1.68M ⊙ ).…”
Section: B Mass-radius Relation and Other Properties Of Neutron Starmentioning
confidence: 99%
“…It was shown that the maximum mass of neutron star is about 1.68M ⊙ . In addition, the EoS with dilaton gravity was employed and the properties of neutron star were investigated [56]. The results showed that by increasing the effects of dilaton gravity, the maximum mass of this star decreases (M max ≤ 1.68M ⊙ ).…”
Section: B Mass-radius Relation and Other Properties Of Neutron Starmentioning
confidence: 99%
“…Finally, substituting eq. (36) back into (35) and into (34), we will get equation of states with fixed temperature and electric charges…”
Section: Thermodynamic Definitions In the Extended Phase Spacementioning
confidence: 99%
“…We will try to understand this question from both thermo-ensemble and dynamical perturbation analysis. While previous works [19,20,[33][34][35][36][37][38][39] are mainly from thermo-ensemble aspects. Our dynamic consideration borrow ideas from ref.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the discovery of a neutron star with mass 1.974M [49]-confirmed later on by other measurements [50][51][52][53], the precise sighting [54] through binary system measurements, double neutron stars features and pulsar systems [55], the validity of GR standard predictions have been indeed put into question. Thus the interest for such configurations in extended theories of gravity, mainly in scalar-tensor theories [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], has aimed to reconcile predictions with astrophysical results.…”
Section: Spherical Configurations: Neutron Starsmentioning
confidence: 99%